Mathematical modeling of penicillin G extraction in an emulsion liquid membrane system containing only a surfactant in the membrane phase - Lee, SC; Chang, JH; Ahn, BS; Lee, WK (ELSEVIER SCIENCE BV, 1998)
An extraction experiment of penicillin G was performed in an emulsion liquid membrane system in which only ECA 4360J exists in the organic membrane phase without a predominant carrier, Amberlite LA-2, used in our previous works and it functions as a carrier as well as a surfactant. A permeation model for the present system has been developed as a primary study to examine the transport mechanism of penicillin G in the previous batch and continuous systems with two carriers of Amberlite LA-2 and ECA 4360J. The model takes into account the mass transfer in the external aqueous film, the extraction reaction between penicillin G and ECA 4360J at the external interface, the diffusion of penicillin G in the emulsion phase, the stripping reaction at the internal interface and the pH change of internal aqueous solution containing Na2CO3 with penicillin G transported into the internal phase. The experimental data were well fitted with the present model. Also, an expression for the reaction of penicillin G with ECA 4360J was obtained through a series of equilibrium measurements in liquid-liquid extraction system. (C) 1998 Published by Elsevier Science B.V. All rights reserved.
Keywords: MASS-TRANSFER